2022
DOI: 10.1007/s41109-022-00488-6
|View full text |Cite
|
Sign up to set email alerts
|

Bots influence opinion dynamics without direct human-bot interaction: the mediating role of recommender systems

Abstract: Bots’ ability to influence public discourse is difficult to estimate. Recent studies found that hyperpartisan bots are unlikely to influence public opinion because bots often interact with already highly polarized users. However, previous studies focused on direct human-bot interactions (e.g., retweets, at-mentions, and likes). The present study suggests that political bots, zealots, and trolls may indirectly affect people’s views via a platform’s content recommendation system's mediating role, thus influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…An other approach mixing recommender systems and opinion dynamics analyzes how these former can be manipulated by bots to influence social media users (Figure 3, topic 5). Pescetelli et al (2022) have demonstrated that bots can shape public opinion indirectly, even without direct human-bot interaction, thanks to their influence on the very workings of a recommendation system. They examine the influence of these entities on shifting average population opinions and manipulating recommendation algorithms' internal representations.…”
Section: 13mentioning
confidence: 99%
“…An other approach mixing recommender systems and opinion dynamics analyzes how these former can be manipulated by bots to influence social media users (Figure 3, topic 5). Pescetelli et al (2022) have demonstrated that bots can shape public opinion indirectly, even without direct human-bot interaction, thanks to their influence on the very workings of a recommendation system. They examine the influence of these entities on shifting average population opinions and manipulating recommendation algorithms' internal representations.…”
Section: 13mentioning
confidence: 99%
“…Although they prove to be efficient, this approach does not scale with the voluminous amount of daily news. To address this issue, alternative automated methods, such as Social Network Analysis, Recommender Systems, Bots, or cross-methodology approaches like Pescetelli et al (2022) can be considered. Hyperpartisan detection may be categorized into three macro-approaches: content, source, and user-based (Pitoura et al, 2017).…”
Section: Definitions and Characteristicsmentioning
confidence: 99%
“…and societies perceive the world and form their opinions [12,21,36,42,44]. In recent years, platforms have come under increasing scrutiny from researchers and regulators alike due to concerns and evidence that their recommendation algorithms create filter bubbles [6,26,28,45] and fuel radicalization [19,27,39,41,49]. One of the main challenges in this context is dealing with content that is considered harmful [4,7,50].…”
Section: Introductionmentioning
confidence: 99%